Energy Management of a Hybrid Electric Vehicle - Khadhraoui, A.; Selmi, T.; Cherif, A. (Engineering, Technology & Applied Science Research, 2022)
Electric Vehicles (EVs) are becoming more popular and gaining attention due to a combination of factors such as falling prices and increasing environmental awareness. EVs fall into several categories related to energy production and storage. Standard developed, tested, and commercialized EV technologies include Fuel Cell Electric Vehicles (FCEVs), All Electric Vehicles (AEVs), also known as Battery Electric Vehicles (BEVs), Plug-in Hybrid Electric Vehicles (PHEVs), Hybrid Electric Vehicles (HEVs), and Flexible Fuel Vehicles (FFVs). Still, the advantages of FCEVs are relatively small compared to other autonomous and refueling technologies. Considering the above aspects, this work presents a Matlab/Simulink model of an FCEV’s behavior and opportunities.